Fleksibilitas Makna Dalam Al-Qur’an - Achmad Khusnul Khitam (Fakultas Adab dan Humaniora UIN Raden Fatah, 2019)
Introduction. Semantic flexibility is one of linguistic phenomenon which represents dynamic relation attached between text, lexical meaning and implied meaning. One of linguistic phenomenon in this issue is technically called semantic shift. In this regard, a word is mentioned but it is intended to something else. Data Collection Method. This article uses two techniques to compile the data; sadap (observation) and catat (notation) techniques. Analysis Data. This article uses semantic approach and analytic descriptive method to analyze the data. Results and Discussions. It is found from this research, that the relation between lexical meaning and implied meaning has many patterns, such as partial relation, causal relation, temporal relation, institution-location relation, etc. From this point, it can be referred that metonimy is similiar to majāz mursal in Arabic rethorical tradition. It is also found that metonimia has some importants secrets on its usage, such as giving power effect on the message, giving firmness and conviction to the audiences and describing the message with real and obvious description. Conslusion. Conclusively, this article found that the Qur’an, as a sacred text in Arabic language does not only use explicit sentences to deliver message, but also uses implicit sentence (majaz) frequently. In fact, it is represented in multi various kinds of relation between text and meaning. Keywords: Semantic shift, flexibility, Metonimy, Qur’an